Compositions of Cu-(Fe)-Sulfides in the 109 Reduced Granite-Related Cu Deposit, Xinjiang, Northwest China: Implications to the Characteristics of Ore-Forming Fluids. (11th February 2020) - Liu, Rui; Chen, Genwen; Yang, Jianxing
Abstract : In general, porphyry Cu deposit is related to the highly oxidized ore-forming system. However, there are many porphyry Cu deposits that are related to the reduced ore-forming system, and the ore-forming characteristics of reduced porphyry Cu deposit are unclear. Cu-(Fe)-sulfides are the main Cu-hosting minerals in porphyry Cu deposits and are also economically important, and the composition of Cu-(Fe)-sulfides has closely relationship with ore-forming characteristics. In this study, concentration data obtained via laser ablation inductively coupled plasma mass spectrometry are reported for chalcopyrite, bornite, and chalcocite from the 109 porphyry Cu deposit formed in a reduced granite-related mineralization system in western Tianshan, Xinjiang, northwest China. The results show that the chalcopyrite hosts several trace elements including Zn, Ge, Se, In, and Sn; the bornite hosts Mo, Ag, Zn, Se, and Bi; and the chalcocite hosts Mo, Ag, Zn, Sn, Se, and Bi. The smooth time-resolved depths profiles and limited variations of trace element concentrations in these sulfides suggest that their presence is isomorphic. The microstructures of the chalcopyrite and bornite were observed by high-resolution transmission electron microscopy. Their lattices are neatly arranged, also indicating that the trace elements exist mainly as isomorphisms in the chalcopyrite and bornite. Ge, Sn, and In are hosted in the chalcopyrite but absent in bornite and chalcocite, indicating that chalcopyrite has a high potential for hosting these elements. Ge and Sn are preferentially hosted in the chalcopyrite, possibly due to relatively high temperatures and low oxygen fugacity during its formation. Indium is preferentially hosted in the chalcopyrite, possibly due to the In 2+ substitution for Fe 2+ controlled by Goldschmidt's rules, which state that substitution occurs between a substituent and host owing to similarities in their radii and charges. However, the concentration of Ag is low in chalcopyrite but significantly high in bornite and chalcocite, indicating that this element is preferentially hosted in the latter two minerals. The abundance of Ag, a low-temperature element, in Cu-(Fe)-sulfides may largely be dependent on temperature. The Au content is below the minimum level of detection in all sulfides, which is obviously different from the classic porphyry copper deposits. In addition, the concentrations of Zn, Ge, As, Sb, and Te in the chalcopyrite and those of Zn, Se, As, Sb, and Bi in the bornite from the 109 porphyry Cu deposit show obvious differences from those of classic porphyry Cu deposits. Therefore, some elements in Cu-(Fe)-sulfides can be used as indicators of ore-forming oxygen fugacity. Bornite and chalcocite are generally enriched in Ag, indicating that the mining of porphyry Cu deposits may be concerned with the precious metal Ag in bornite and chalcocite. In addition, chalcopyrite may host sufficient Se and Zn, and bornite and chalcocite could host sufficient Se, Zn, and Bi, suggesting that sulfides may be hosts for deleterious elements.